A Novel Potassium‐Ion‐Based Dual‐Ion Battery. Issue 19 (15th March 2017) - Ji, Bifa; Zhang, Fan; Song, Xiaohe; Tang, Yongbing
Abstract : In this work, combining both advantages of potassium‐ion batteries and dual‐ion batteries, a novel potassium‐ion‐based dual‐ion battery (named as K‐DIB) system is developed based on a potassium‐ion electrolyte, using metal foil (Sn, Pb, K, or Na) as anode and expanded graphite as cathode. When using Sn foil as the anode, the K‐DIB presents a high reversible capacity of 66 mAh g −1 at a current density of 50 mA g −1 over the voltage window of 3.0–5.0 V, and exhibits excellent long‐term cycling performance with 93% capacity retention for 300 cycles. Moreover, as the Sn foil simultaneously acts as the anode material and the current collector, dead load and dead volume of the battery can be greatly reduced, thus the energy density of the K‐DIB is further improved. It delivers a high energy density of 155 Wh kg −1 at a power density of 116 W kg −1, which is comparable with commercial lithium‐ion batteries. Thus, with the advantages of environmentally friendly, cost effective, and high energy density, this K‐DIB shows attractive potential for future energy storage application. Abstract : A novel dual‐ion battery based on potassium‐ion electrolyte (K‐DIB) is developed in this work using metal foil as both anode and current collector and expanded graphite as cathode. The K‐DIB based on Sn foil anode presents a capacity of 66 mAh/g over 3.0–5.0 V, and exhibits a capacity retention of 93% after 300 cycles. Moreover, it delivers a energy density of 155 Wh/kg at a power density of 116 W/kg, comparable with commercial lithium‐ion batteries.